Eksplorasi Kebiasaan Gen-Z dalam Menggunakan AI untuk Beraktivitas Sehari-Hari - Rahmadani, Silvi; Rizky, Divia Zal; Aini, Nurul (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to determine Generation Z’s habits in using artificial intelligence (AI) technology in their daily lives. The background to this research is the increasing use of AI in various activities, particularly among the younger generation who are familiar with technology. This study used a descriptive quantitative approach with an online questionnaire survey method. The sample was drawn using an accidental sampling technique and successfully collected 107 respondents from Generation Z. The results show that the majority of respondents are familiar with and use AI regularly, whether for learning, finding assignment references, entertainment, or other purposes. ChatGPT was the most widely used platform, followed by Google Assistant, Canva, and Capcut. Most respondents found AI helpful, although some felt they were starting to become dependent. When searching for information, many respondents used AI and Google simultaneously, depending on their needs and topics. In conclusion, Generation Z is quite familiar with AI and utilizes it in various activities. However, the use of AI still requires a good understanding and a wise attitude for its use to have a positive impact.